Mapping and panorama of cattle slaughterhouses in Santa Catarina State - Cucco, Diego de Córdova (2021)
Generally, in Brazil there is no connection between sectors of the beef catle producton chain, such as producers, slaughterhouses and consumers. There is a lack of informaton about the profile of slaughtered catle and market’s demand, which ends up not being identified the real situaton of the chain. The objectve of this study was to map the most relevant slaughterhouses in Santa Catarina registered with the federal, state and municipal inspection services and research the slaughter situation with them, your demands and desires. Afer collecton and data analysis, it was clear that the establishments do notreach full daily slaughter capacity and slaughter animals of less than desired quality, with scarce fnish and in some cases dairy catle, for lack of supply. It was possible to know and better understand this link in the chain, with that we can orientate farmersproducton to meet the market’s demands.